Understanding patient and family utilisation of community-based palliative care services out-of-hours: Additional analysis of systematic review evidence using narrative synthesis. - Joanna Goodrich; Caleb Watson; Inez Gaczkowska; Richard Harding; Catherine Evans; Alice Firth; Fliss E M Murtagh (PLoS ONE)
Background Community-based out-of-hours services are an integral component of end-of-life care. However, there is little understanding of how patients and families utilise these services. This additional analysis of a systematic review aims to understand and identify patterns of out-of-hours service use and produce recommendations for future service design. Method Data on service use was extracted and secondary analysis undertaken, from a systematic review of models of community out-of-hours services. Narrative synthesis was completed, addressing four specific aspects of service use: 1.Times when patients/families/healthcare professionals need to contact out-of-hours services; 2. Who contacts out-of-hours services; 3. Whether a telephone call, centre visit or home visit is provided; 4. Who responds to out-of-hours calls. Results Community-based out-of-hours palliative care services were most often accessed between 5pm and midnight, especially on weekdays (with reports of 69% of all calls being made out-of-hours). Family members and carers were the most frequent callers to of the services (making between 60% and 80% of all calls). The type of contact (telephone, centre visit or home visit) varied based on what was offered and on patient need. Over half of services were led by a single discipline (nurse). Conclusions Out-of-hours services are highly used up to midnight, and particularly by patients' family and carers. Recommendations to commissioners and service providers are to: • Increase provision of out-of-hours services between 5pm and midnight to reflect the increased use at these times. • Ensure that family and carers are provided with clear contact details for out-of-hours support. • Ensure patient records can be easily accessed by health professionals responding to calls, making the triage process easier. • Listen to patients, family and carers in the design of out-of-hours services, including telephone services. • Collect data systematically on out-of-hours-service use and on outcomes for patients who use the service.